1996
DOI: 10.1074/jbc.271.37.22908
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heterogeneous βA4 Peptides in Human Cerebrospinal Fluid and Blood by a Newly Developed Sensitive Western Blot Assay

Abstract: The betaA4 peptide, a major component of senile plaques in Alzheimer's disease (AD) brain, has been found in cerebrospinal fluid (CSF) and blood of both AD patients and normal subjects. Although betaA4 1-40 is the major form produced by cell metabolism and found in CSF, recent observations suggest that the long-tailed betaA4 1-42 plays a more crucial role in AD pathogenesis. Here, we established new monoclonal antibodies against the C-terminal end of betaA4 1-40 and 1-42, and used them for the specific Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
389
3
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 483 publications
(410 citation statements)
references
References 43 publications
(29 reference statements)
15
389
3
3
Order By: Relevance
“…Samples were transferred to fresh eppendorf tubes, incubated on ice for 15 min and centrifuged at 13000 rpm at 4°C for 10 min. 13A4 in the supernatant (cell lysate) was first immunoprecipitated with anti-13A4 monoclonal antibody (clone W0-2 [13]) and protein G-agarose (Boehringer Mannheim, Germany), and analyzed by Western blotting.…”
Section: Analysis Of Cell-associated [Ia4mentioning
confidence: 99%
See 2 more Smart Citations
“…Samples were transferred to fresh eppendorf tubes, incubated on ice for 15 min and centrifuged at 13000 rpm at 4°C for 10 min. 13A4 in the supernatant (cell lysate) was first immunoprecipitated with anti-13A4 monoclonal antibody (clone W0-2 [13]) and protein G-agarose (Boehringer Mannheim, Germany), and analyzed by Western blotting.…”
Section: Analysis Of Cell-associated [Ia4mentioning
confidence: 99%
“…Western blot detection and quantitation of [3A4 was performed as described elsewhere [13]. Briefly, heat-denatured samples were separated by 10-20% or 16% Tris-Tricine SDS-PAGE.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies demonstrated that the levels of CSF Aβ42 in AD are decreased compared with controls [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] . CSF Aβ42 can differentiate AD from controls with 89% sensitivity and 90% specificity [51] .…”
Section: Csf Aβ42 As a Biomarker Of Admentioning
confidence: 99%
“…2 In peripheral blood, the major species is Aβ40. 4 Soluble Aβ oligomers impair neuronal function by altering the expression of memory-related receptors, 5 inducing aberrant neuronal responses to electrical stimulation 6 and inducing neural death. 3,7 Aβ has emerged as a promising target for immunotherapeutic intervention in AD.…”
Section: Immunotherapy Of Alzheimer Disease (Ad)mentioning
confidence: 99%